2017
DOI: 10.2147/tcrm.s143845
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic findings of thoracic trauma

Abstract: IntroductionChest trauma may be blunt or penetrating and the chest is the third most common trauma region. It is a significant cause of mortality. Multidetector computed tomography (MDCT) has been an increasingly used method to evaluate chest trauma because of its high success in detecting tissue and organ injuries. Herein, we aimed to present MDCT findings in patients with blunt and penetrating chest trauma admitted to our department.MethodsA total of 240 patients admitted to the emergency department of our h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Most of PC were bilateral, what is in disagreement with previous studies, that evidence a slight [16,28] or vast [23,29] predominance of unilateral PC. Bilateral PC are more frequent in children who suffer traffic accidents compared to others injury mechanisms [26] and our data showed that falls generally were related to bilateral lesions and responsible for a significant percentage of PC.…”
Section: Distribution Of Opacitiescontrasting
confidence: 99%
See 1 more Smart Citation
“…Most of PC were bilateral, what is in disagreement with previous studies, that evidence a slight [16,28] or vast [23,29] predominance of unilateral PC. Bilateral PC are more frequent in children who suffer traffic accidents compared to others injury mechanisms [26] and our data showed that falls generally were related to bilateral lesions and responsible for a significant percentage of PC.…”
Section: Distribution Of Opacitiescontrasting
confidence: 99%
“…[12] Therefore, CT can be assumed as a gold standard method. [13][14][15][16] The image pattern described in the literature is patchy or nonsegmental alveolar opacities, ranging from patchy ill-defined ground-glass opacities (GGO) to extensive areas of mixed lesions or consolidations. [2] Among the characteristics that can help to differentiate it from others airspace diseases are subpleural sparing, which is described as the noninvolvement of 1 to 2 mm of pulmonary parenchyma beneath the pleura [17] and their tendency to not respect anatomic limits, including pulmonary fissures, since they originate from the application of external forces on the pulmonary parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also concluded, perhaps in keeping with the finding that greater force is needed to penetrate cartilage and bone, that fractures to the ribs are not common in penetrating trauma [22].…”
Section: Ta B L Ementioning
confidence: 68%
“…Other studies have also concluded, perhaps in keeping with the finding that greater force is needed to penetrate cartilage and bone, that fractures to the ribs are not common in penetrating trauma [22]. One large cross‐sectional study, examining rib fractures in chest trauma, found that rib fractures occurred in just 32.7% of cases of penetrating trauma [23].…”
Section: Discussionmentioning
confidence: 87%
“…Chest is the third most common anatomic region for trauma and considering penetrating mechanism, it has approximately 40% mortality. Although, according to previous studies, nail gun injury has less mortality rate (25%), its rarity makes its diagnosis crucial [ 1 , 3 , 4 ]. Therefore, early vigilant clinical assessment of the patients, and employment of imaging modalities among those with hemodynamic stability, can play a key role in the precise characterization of the injury especially considering rare causes like nail gun injury.…”
Section: Discussionmentioning
confidence: 99%